Seismo-Stratigraphy and Sedimentology of Holocene Sediments off Grande Rivière de la Baleine, Southeastern Hudson Bay, Québec - Gonthier, Nicole; d’Anglejan, Bruno; Josenhans, Heiner (Géographie physique et Quaternaire, 1993)
ABSTRACTThe regional distribution of Holocene sediments of eastern Hudson Bay off the Grande Rivière de la Baleine mouth was mapped using a grid of reflection seismic lines (approximately 300 km long and covering an area of approximately 800 km2) and data from 7 piston cores. Based on the seismic records and piston cores, 4 stratigraphic units overlying the Proterozoic bedrock (unit 1) were defined and interpreted: (unit 2) glacial till deposited by a westward flowing ice sheet, (unit 3) rhythmically bedded clays and silts presumably deposited in glacial Lake Ojibway, (unit 4) postglacial marine muds deposited in the Tyrrell Sea overlain by undifferentiated modern marine muds, and (unit 5) distal fluviodeltaic sediments from Grande Rivière de la Baleine. Similar stratigraphie units have been described onshore. Textural and geochemical analyses suggest that unit 3 rhythmites are true varves; dark "summer" laminae were deposited mainly by underflows during the open water season, and light "winter" laminae were deposited by overflows-interflows along thermal stratifications under a seasonal ice cover. Unit 5 covers approximately 400 km2 and occurs as a deltaic constructional wedge protruding as far as 11 km offshore of the Grande Rivière de la Baleine entrance with thicknesses reaching 30 m along the coast. It was deposited between 3500 BP and the present from remobilization of glacial sediments farther upstream due to river downcutting during emergence.